Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Nurlaelasari, Nurlaelasari; Degita , Azolla; Prasetia, Angga (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The aim of this research is to examine the influence of profitability (X1) and company size (X2) on company value (Y). This research is a type of quantitative research. The data source used is secondary data. The sample in this research is food and beverage companies listed on the Indonesian stock exchange. The samples for this company were 20 sample companies with an observation period of three years (2020-2022), namely 60 sample units. The results obtained show that profitability has a positive effect on company value. This is because profitability is effective in a company so that it can generate profits from its operational activities, and company size has a negative effect on company value. It is because of the size of the company that large companies cannot guarantee high company value because they do not dare to make new investments before they pay their debts